A crise do estado investidor e as privatizações no Brasil e na Argentina (1990 - 1999) - Teixeira, Josélia Elvira (2006)
This work aims at analyzing the main factors that triggered off the crisis of the Investor State and the programs of privatizations in Brazil and Argentina between the years of 1990 and 1999. The comprehension of the State s crisis is limited to its incapacity of investment. It is used the deductive method in the analysis, since it comes from external and internal factors, that influenced the crisis in the investor State. Among the Washington s Consensus recommendations (1989) there were the privatizations, which were used in both countries as a link in the State reform and used to help the economic politics for the economy stabilization, attraction of external investments and to achieve the credibility of the international business community. In Argentina, the President Carlos Menem started the privatizations with two big companies: ENTEL and Argentinean Airlines. Differently from Argentina, in Brazil it was created the National Program of Non-Nationalization and the privatizations were started by sectors of industries such as steel industry, petrochemicals and fertilizers, observing that the privatization of the service sector was only constitutionally allowed after 1995. However, both countries privatized many state companies in several different sectors of economy, besides cutting subsidies off private sectors and decreasing public expenses, being the stability of currency the biggest conquest.